Preoperative Anti-Class III β-Tubulin Antibodies As Relevant Clinical Biomarkers in Ovarian Cancer - Enrica Martinelli; Andrea Fattorossi; Alessandra Battaglia; Marco Petrillo; Giuseppina Raspaglio; Gian Franco Zannoni; Mara Fanelli; Daniela Gallo; Giovanni Scambia (Translational Oncology, 2018)
Class III β-tubulin (TUBB3) overexpression in ovarian cancer (OC) associates with poor prognosis. We investigated whether TUBB3 overexpression elicited anti-TUBB3 antibody production in OC patients and whether these antibodies may have diagnostic and prognostic impact. The presence of serum anti-TUBB3 antibodies was investigated in 49 untreated OC patients and 44 healthy individuals by an in-house developed ELISA that used recombinant TUBB3 as the antigen. Receiver operating characteristic (ROC) curves were generated to assess the diagnostic accuracy of the assay. Anti-TUBB3 antibodies discriminated OC patients and healthy individuals with excellent sensitivity and specificity (91.8% and 90.9%, respectively). In multivariate analysis, anti-TUBB3 antibody level emerged as an independent prognostic factor for progression free and overall survival. The ELISA was then optimized using a biotin-labeled TUBB3 C-terminal peptide424-450 instead of recombinant TUBB3 as the antigen and streptavidin-coated plates. The diagnostic role of the anti-TUBB3 antibodies was studied in an independent series of 99 OC patients and 80 gynecological benign disease patients. ROC-curve analysis showed a valuable diagnostic potential for serum anti-TUBB3 antibodies to identify OC patients with higher sensitivity and specificity (95.3% and 97.6%, respectively). Overall, our results provide evidence that preoperative anti-TUBB3 antibody level is a promising diagnostic and prognostic biomarker for the management of OC patients.